Caregiver’s quality of life in advanced cancer: validation of the construct in a real-life setting of early palliative care - Borelli, Eleonora; Bigi, Sarah; Potenza, Leonardo; Gilioli, Fabio; Efficace, Fabio; Porro, Carlo Adolfo; Luppi, Mario; Bandieri, Elena (Frontiers in Oncology, 2023)
Introduction: Early palliative care (EPC) improves the quality of life (QoL) of advanced cancer patients and their caregivers. The increasingly widespread use of this care model requires the development of measures supporting its interventions. Although the construct of patient’s QoL has been extensively investigated and several QoL measures have been further validated, there is a paucity of data concerning the QoL of the caregiver. In 2018, McDonald and colleagues addressed this issue by interviewing 23 primary caregivers of advanced cancer patients who participated in an EPC randomized clinical trial to understand their perspective on the QoL construct. The Authors identified six major dimensions associated with the construct of caregiver’s QoL. The present retrospective study aimed to validate these dimensions on a larger sample and in a real-life EPC setting. Methods: Previously collected reports from 137 primary caregivers of advanced cancer patients on EPC answering questions about their experience with this care model were qualitatively analyzed through a deductive, thematic approach to identify and confirm the six dimensions constituting the construct of interest based on McDonald’s and colleagues' results. Results: The six dimensions (“living in the patient’s world”, “burden of illness and caregiving”, “assuming the caregiver role”, “renegotiating relationships”, “confronting mortality”, and “maintaining resilience”) were consistently found in the reports from primary caregivers in a real-life EPC setting, confirming to be significant themes associated to their QoL. Conclusion: A definite and recurrent construct of primary caregiver’s QoL as described by McDonald and colleagues was also found in a larger sample and in a real-life EPC setting. Thus it may lay the groundwork for the development of a dedicated questionnaire.